"Quantity Itself Generates Quality": Family Conceptions Between Catholicism, Nationalism, and Eugenics in Slovakia in the Late 1930s and Early 1940s. (July 2023) - Szabó, Miloslav
This study deals with the intersections but also the unrelenting tension between the Catholic Church und politics and efforts to regulate society through eugenics in order to heal it in the context of the establishment of the Slovak state between 1938 and 1941, which was based on a specific conception of traditional family. In the first step, the discourse of the national revolution in the period of Slovak autonomy at the turn of 1938 and 1939 is analyzed, with emphasis on the requirement of "national health" through measures of so-called positive eugenics. Subsequently, the article examines the efforts to institutionalize this discourse in the context of the establishment of a museum of hygiene according to the German model. Finally, it outlines the impact of this context on the preparation and implementation of the anti-interruption law on "fetal protection" of 1941.